“Don’t Touch Your Face!” The Contribution of Habit Reversal in the COVID-19 Pandemic - Simone Varrasi; Sabrina Castellano; Giuseppe Alessio Platania; Claudia Savia Guerrera; Pasquale Caponnetto; Concetta Pirrone (Health Psychology Research, 2022)
The Habit Reversal Training (HRT) is a behavioral procedure for treating the so-called nervous habits, such as nail biting, hair pulling and thumb sucking. In addition to being an established clinical procedure, HRT is also a strategy for behavioral change that can serve the entire community. For this reason, this review aims to explore the studies proposing the use of HRT for the reduction of hand-to-face habits in the context of COVID-19 pandemic. Touching one's nose, mouth and eyes, indeed, is one of the means of virus transmission that many awareness campaigns seek to highlight. After an overview of how HRT works and of the current epidemiological situation, studies supporting Habit Reversal Training for the reduction of risky hand-to-face habits are presented. The possible strategies are then exposed and critically discussed to identify their limitations and propose a new version according to the Relational Frame Theory.